ANALISIS KELAYAKAN TATA MASSA DAN FASAD RUMAH TROPIS MODERN BERDASARKAN UNIFORM BUILDING BY-LAWS (UBBL) DI MALAYSIA - Ahmad Affan Firza Alfian; Fadila Fitria Wulandari; Ahmad Rofif Hidayatullah; Ahmad Zaim Zamroni; Alfath Ibrahimovich; Tee Tze Kiong (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study explores the compliance of modern tropical house design in Malaysia with the Uniform Building By-Laws (UBBL) 1984, highlighting challenges arising from differences in construction regulations between Indonesia and Malaysia, despite both countries having similar tropical climates. The research focuses on a comparative evaluation of a prototype design, including building massing, natural lighting, and natural ventilation. The evaluation shows that the design meets structural requirements, with well-organized massing that does not exceed building setback limits. Although the lighting ratio in the master bedroom is slightly below the standard, this adjustment is intended to reduce heat gain in a tropical climate context. The ceiling height of 2.75 meters meets the minimum standard and supports thermal comfort. In conclusion, the modern tropical house design demonstrates architectural and legal feasibility for implementation in Malaysia, emphasizing the importance of harmonizing aesthetics with local regulatory compliance.